The impact of labour market accessibility on housing prices - Liv Osland; Inge Thorsen; Jens Petter Gitlesen (European Regional Science Association (ERSA), 2004)
In this paper we study the relationship between labour market accessibility and housing prices in a Norwegian region. Through a hedonic approach we estimate implicit prices for a location with a marginally improved labour market accessibility. We test alternative measures of spatial separation between residential location alternatives and job opportunities. Gravity based accessibility measures in general improve model performance compared to a standard approach with one-dimensional measures of distance. We also discuss how sensitive the results are with respect to the delimitation of the geography. Based on our empirical results we finally enter into the discussion of how changes in the transportation infrastructure and the spatial distribution of employment opportunities capitalise through property values.
Keywords: 330